Effect of ZnO addition on ferroelectric properties of 0.94Pb(Fe1/2Nb1/2)O3-0.06PbTiO3 and 0.9Pb(Fe1/2Nb1/2)O3-0.1PbTiO3 ceramics. Issue 187 (12th February 2018) - Wattanasarn, H.; Photankham, W.; Kongpimai, J.; Thanachayanont, C.; Yimnirun, R.
ABSTRACT: Relaxor and ferroelectric materials are outstanding for electronic application, indicating kind of ferroelectric material is still ambiguously due to different behavior of stoichiometric ratio of precursors. The samples of 0.94Pb(Fe1/2 Nb1/2 )O3 -0.06PbTiO3 (PFNT94/6) and 0.9Pb(Fe1/2 Nb1/2 )O3 -0.1PbTiO3 (PFNT90/10) were mixed with ZnO at 0, 1, 2, and 3 wt.%, and were synthesized using mixed oxide. Phase transition and microstructure were analyzed by using X–ray diffractometer (XRD) and SEM technique, respectively. The results showed that PFNT94/6-xZnO and PFNT90/10-xZnO shifted to tetragonal phase and suppressed pyrochlore phase when increasing ZnO content. Grain size decreased with increasing ZnO contents in range of 0.89–2.18 µm of PFNT94/6 due to coarsening processes dominate, the production of a highly porous is easily be found and decreased the average grain size, conversely, grain size increased with increasing ZnO contents in range of 3.15–11.52 µm of PFNT90/10. The PFNT94/6 exhibits broaden peak of dielectric constant, meanwhile, the dielectric constant maximum temperature at 144°C of PFNT90/10. The dispersion of dielectric constant decreases with increasing ZnO contents. The relaxor ferroelectric of PFNT90/10 ceramic shifted to normal ferroelectric with increasing ZnO contents. Ferroelectric properties were investigated on polarization electric field, polarization of PFNT94/6 exhibited relaxor ferroelectric at low field, PFNT90/10 showed normal ferroelectric as well as endurable breakdown. The relaxor ferroelectric material can be modified to ferroelectric material by adding ZnO.